Comportamento fisiológico e bioquímico de sementes e grãos de feijão durante o armazenamento. - Cassol, Flavia Danieli Rech (2013)
Beans are one of the foods used to supply the energy needs of the Brazilian diet, so it is necessary that farmers use high seed physiological potential, capable of increasing crop productivity. Thus, the aim of this study was to evaluate the physiological and biochemical changes occurring in beans stored for 360 days. Analyses were performed at 0, 30, 90, 180, 270, and 360 days after receiving the seeds (S1 and S2) and grains (G1 and G2) of BRS Radiance, coming from two producers. Tests of germination, accelerated aging, cold, and index of germination speed (IVG), average length of shoot (CMPA) and of root (CMR), electrical conductivity and the electrical conductivity of the leachate were quantified in levels of sugars and amino acids, in addition to Ca, K, Mg, Mn, Fe, and Zn. The experimental design was completely randomized split-plot in time and the means were compared by the Tukey test at 5% probability. Seed germination was not affected in S2, while S1 and G1 showed a significant fall. The grains from field 1 had a greater influence on heat, stress, and cold, with its vigor decreasing from 91 to 50% and from 93 to 76%, respectively, after 360 days. The IVG tests presented decreased during the experiment. The CMPA and CMR samples showed variations during the experiment, and G1 had the lowest means. In electrical conductivity greater loss of solutes occurred at 90 days of evaluation. Up to 180 days of storage, G1 presented higher amount of amino acids and at 360 days the greatest value S1. Larger amount of soluble sugars were found in samples from field 1. The amount of calcium ions, manganese, iron, and zinc found in the samples were very small. The amounts of potassium decreased until 360 days of storage, and G1 showed the highest value. After 90 days the amounts of magnesium of the samples increased considerably. The grains from field 1 had lower physiological quality. The tests of accelerated aging, cold, and IVG showed a drop in vigor of the Splendor BRS, whereas the electrical conductivity test was not sensitive enough to detect this decrease. This test did not present association with the quantification of the ions investigated. The amount and behavior of amino acids, sugars the ions studied in this work, failed to relate these variables to the decrease in vigor of the bean samples. The storage period influenced the physiological quality of the beans tested.